Promoting Your Educational Material as Scholarship: The MedEdPORTAL Project - Sandy Cook (Association of American Medical Colleges, 2005)
Abstract This is a workshop assessment tool designed to help faculty publish their educational materials via MedEdPORTAL. This interactive, hands-on workshop can be presented as a 2-hour interactive session to familiarize faculty with MedEdPORTAL and, by considering their own educational scholarship, help them determine which products are suitable for submission. Participants will review MedEdPORTAL's submission standards, choose material to submit, review the MedEdPORTAL submission form, review the MedEdPORTAL peer review form, and complete an evaluation of the workshop. The time frame can vary depending on how many people are in attendance, how much detail is needed to explain the MedEdPORTAL process, how advanced individuals are in the preparation of their material, and whether time is taken to actually begin to resolve some of the barriers or work on completing the material. Preliminary analysis of the first workshop suggested that faculty participants liked the idea of tying workshop assessment to commitemnts. Participants were willing to complete the form and make reasonable commitemnts.